Defining success in regional anaesthesia. (10th January 2021) - Johnston, D. F.; Turbitt, L. R.
Summary: Utilisation of regional anaesthesia is increasing globally; however, it remains challenging to determine the overall benefit of individual regional anaesthesia procedures. Like any peri‐operative intervention, the benefit to the patient and healthcare system must outweigh any patient risk or resource implications. This review aims to identify markers of success in regional anaesthesia, categorise these into an objective framework and rationalise suggestions on how measuring outcomes in regional anaesthesia can be used to develop the widespread performance of this evolving subspecialty. This framework of measuring success of regional anaesthesia contains four pillars: patient‐centred, population‐centred, healthcare‐centred and training‐centred outcomes. Each pillar of success contains several outcomes which provide a structure for the measurement and development of regional anaesthesia success on a global scale.